FORMULATION DEVELOPMENT, CHARACTERIZATION AND IN- VITRO EVALUATION OF FLOATING MATRIX DOSAGE FORM OF TRAMADOL HYDROCHLORIDE USING VARIOUS POLYMERS - Anepu, Sarada; Duppala, Lohithasu; M, Soma Sundari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of present study was to formulate the gastro retentive floating tablets of tramadol hydrochloride for enhancement of the gastric residence time. Methods: The floating tablets were prepared by direct compression method and evaluated for hardness, thickness, and friability of the tablets. The in vitro drug release studies were performed for different formulations and to optimize the best formulae based on the dissolution profiles. Results: Fourier transform infrared spectroscopy and differential scanning calorimetry studies revealed that there was no interaction between tramodol hydrocholride and excipients. The formulated tablets were evaluated for properties like weight variation, hardness, thickness, friability, drug content, density and floating properties, matrix integrity and complied with USP requirements. The tablets of optimized formula had floating lag time of 120, 72 and 96 seconds and the tablets remained in the floating condition for more than 12 h. The results of drug excipients compatibility studies suggest that there was no significant change in the physical appearance of these blends, when stored at 40 Â°C/75% RH for a period of 4 weeks.Â Among various trial formulations developed with different concentration of polymer F3 (HPMC K4 M with 120mg of polymer), F5 (HPMC K15 M with 100 mg polymer), F11 (PEO WSR 303 with 100mg polymer), were chosen as the optimized formulations based on the release profile. Conclusion: Tramodol HCl floating tablets were successfully made using various polymers for the enhancement of the gastric residence time. From the present study it was concluded that hydroxy propyl methyl cellulose K 4 M can be used as effective polymer for the formulation of floating effervescent tablets of highly soluble drug indicating successful development of sustained release floating drug delivery system. Key words: Tramodol HCl, floating tablets, PEO 303 WSR, PEO N60, HPMC K 4 M, HPMC K15 M and HPMC K 100 M.Â